2016
DOI: 10.1016/j.gdata.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis is accompanied by lack of KIR2DS1 gene: A meta-analysis

Abstract: Multiple sclerosis (MS) is a disease in which we can recognize destruction of the myelin that is around nerve cells of brain and spinal cord called as oligodendrocytes. Both genetic and environmental factors play roles in MS. One of these genes is the killer-cell immunoglobulin-like receptor (KIR) which expressed on surface of natural killer cells (NKs). These genes have loci (not locus) in human genome, so they inherit as haplotypes. The results of previous studies show that different genes of KIR may affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Other than the justification above, another justification is that the ligands of activating KIRs are not necessarily HLAs; rather, they are still unknown [36], [53]. This, can be pointed out as the limitation of the previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than the justification above, another justification is that the ligands of activating KIRs are not necessarily HLAs; rather, they are still unknown [36], [53]. This, can be pointed out as the limitation of the previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Killer cell immunoglobulin-like receptors (KIRs) (also called as CD158) are polymorphic glycoproteins expressed on cell surface of NKs and T cell subsets [35]. KIR gene family is highly polymorphic and its genomic diversity is achieved through differences in gene content as well as allelic polymorphism [36], [37]. Of course the most polymorphic loci in human genome is HLA [38] which the molecules of its, are in direct contact with KIR molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In the Sardinian population, MS has been found associated with the HLA-A*30, -B*18, -C*05, -DR*03 extended haplotype and the HLA-DR*03 and HLA-DQ*02 alleles [30, 31]. While many authors link MS to the HLA system, only a minority of studies have reported association between MS and KIR genes and the results are either contradictory or remain unconfirmed [3234]. All these studies applied standard statistical tests which are useful in detecting single alleles and/or haplotypes that either confer protection or susceptibility to disease.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first meta-analysis that examines KIR effects on HIV acquisition. By extension, associations of the KIR polymorphisms have been reported in a number of meta-analyses that included disease endpoints such as systemic lupus erythematosus, rheumatoid arthritis, type 1 diabetes mellitus and multiple sclerosis [5457]. The only other meta-analysis for KIR polymorphisms with another infectious disease is that of Gauthiez et al’s examination of the Hepatitis C Virus (HCV) infection with HCV clearance [58].…”
Section: Discussionmentioning
confidence: 99%